Event shape distribution and the NLP corrections - Agarwal Neelima; van Beekveld Melissa; Laenen Eric; Mishra Shubham; Mukhopadhyay Ayan; Tripathi Anurag (EPJ Web of Conferences)
For the event shapes thrust and c-parameter at next-to-leading order, we examine the origins of next-to-leading power corrections. We track down the origin of these factors for each shape of the event and compare our findings with a recent method that makes use of the eikonal approximation and momentum changes derived from the Low-Burnett-Kroll-Del Duca theorem. We do an analytical and numerical analysis of the differences. Both precise and approximate findings are described in terms of elliptic integrals for the c-parameter; yet, it exhibits patterns that are similar to those observed in the thrust results near the elastic limit.